Studying the Passivity and Breakdown of Duplex Stainless Steels at Micrometer and Nanometer Scales – The Influence of Microstructure - Pan, Jinshan (Frontiers in Materials, 2020)
Duplex stainless steels (DSSs) consist of ferrite and austenite phases with approximately equal volume fraction. They exhibit combined superior mechanical strength and corrosion resistance, therefore are increasingly used in various applications. However, under certain conditions, passivity breakdown may occur, leading to corrosion initiation, which is often related to weak points in the heterogeneous microstructure. To understand the influence of microstructure on the passivity and breakdown of DSSs requires local probing techniques that can be used in situ, so that corrosion initiation process can be correlated to the microstructure. Recent studies employing advanced scanning probe microscopy and synchrotron-based techniques, in combination with electrochemical measurements, have contributed to a deep understanding of the passive film, passivity breakdown, and corrosion initiation of DSSs, as well as the influence of microstructural and environmental factors. This mini review presents a short summary of recent literature focusing on the studies utilizing local probing techniques and synchrotron-based analyses.